On the discrete time-varying JLQG problem - Czornik, Adam; Świerniak, Andrzej (1950- ) (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper optimal time-invariant state feedback controllers are designed for a class of discrete time-varying control systems with Markov jumping parameter and quadratic performance index.
Keywords: jump linear systems; optimal control; time-varying systems; coupled Riccati equations